Training Abroad on Developing E-portfolio for Thai Teachers: Lessons Learned - Ali, Raden Muhammad; Hastuti, Dwi; Azhari, Ahmad; Biddinika, Muhammad Kunta (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
International programs by university lecturers in Indonesia, both research and community service, are currently highly encouraged. This kind of international program is believed to provide many benefits such as: increasing cooperation networks both academically and non-academically. In its implementation, not all international programs run smoothly as planned. There are various problems faced by the organizers caused by differences in language, culture, rules, etc. This article will reveal the author's experience in organizing an international training program on developing electronic portfolio ( e-portfolio) especially for English and Arabic teachers in Thailand, covering challenges and lessons learned that come with it. This study uses a qualitative narrative approach with data collection through observation, interviews, and documentation. The data analysis technique is based on the theory of Miles and Huberman which includes: data reduction, data display, and conclusion drawing/verification. The findings of this study are the constraints and lessons that can be drawn from this training. Some of the obstacles faced are preparation that requires sufficient time, language barriers, and differences in culture and rules in the two countries. Some lessons that can be taken from this experience are: international programs require sufficient time and careful preparation, it needs language mastery for facilitators according to the language of the trainees, and the rules and culture of the partner country or school need to be understood so that there is no misunderstanding between the organizer and the partner. Keywords : international program, electronic portfolio, training for teachers, challenges, lessons learned